About our ancestors; the Japanese family system, - Kunio, Yanagita (Japan Society for the Promotion of Science [distributed by Kinokuniya Book-store, 1970)
The Object this book is mainly Yanagita Kunio and " About our Ancestors" : two kinds of meanings, a single illustration, the founder of one family, becoming an ancestor,...